EVALUATION OF SOLITARY POLYPOID MASS IN COLORECTAL REGION WITH CLINICAL PATHOLOGICAL CORRELATION. - Ragini Gupta; Sandhya Kumari Sinha (Student's Journal of Health Research, 2023)
Objectives: We conducted this research to comprehensively evaluate solitary polypoids in the colorectal place by conducting a clinicopathological correlation. We aimed to determine the medical and pathological characteristics of those masses, their incidence, and the affiliation among clinical findings and histopathological features. Methods: A retrospective evaluation of patients who offered solitary polypoid masses within the colorectal area at Patna in a tertiary care centre. Inclusion criteria encompassed patients with showed colorectal polyps primarily based on endoscopic findings. Biopsy specimens acquired during endoscopic approaches have been subjected to histopathological examination. Statistical evaluation, inclusive of chi-rectangular assessments or logistic regression, is performed as appropriate to determine massive correlations. Results: Among the polyps studied, 60% were identified as adenomatous, 25% as hyperplastic, 10% as serrated, and 5% as inflammatory subtypes. Additionally, 18% of adenomatous polyps exhibited high-grade dysplasia, indicating an accelerated chance of malignancy. A  statistically enormous association between patient age and the chance of adenomatous polyps (p < 0.05), with older patients being more at risk of adenomatous lesions. Conclusion: The prevalence of adenomatous polyps and the presence of high-grade dysplasia among them reaffirm the want for vigilant tracking and intervention. These outcomes contribute to the developing frame of proof helping early detection and tailor-made control strategies for colorectal pathologies, ultimately aiming to enhance patient effects and reduce the weight of colorectal malignancies. Recommendation: More such studies are required and physicians need to take studies into consideration while assessing the symptoms and deriving the diagnosis of the study.